Saeculum-Mundus Politik Indonesia: Satu Kajian Filosofis dalam Perspektif Nurcholish Madjid - Imron Mustofa (Hayula: Jurnal Indonesia Studi Islam Multi-disiplin, 2021)
This article suggests some common opinions on Muslim’s worldview, which became the center of contention. This gives rise to perspective which states that the religion participation in government will bring the world of politics into the arena of theo-centrism that ends in authoritarianism. The research is qualitative, based on library research. The approach used is descriptive critical analysis. It aims to describe factual dynamics on Indonesian social-politic from philosophical point of view. The research finds that, on the second half of twentieth century, Nurcholish Madjid’s renewal idea on Islamic political thought (secularization) gets a variety of responses. Madjid suggested the need to separate religion from social-politic arena with his slogan, ‘Islam Yes, Islamic party No’. The basis of the idea is built on the concept of rationality as the main authority in the social science paradigm. Ideas or dogma, meanwhile, is part of historical development which has to be submissive to conditions that always change. Everything that “exist” has to change, the only absolute one is the change itself.